G216 A Meta-Analysis of "Wii Therapy" in Children with Cerebral Palsy. (4th June 2013) - Farr, W; Male, I
Abstract : Aims: There has been growing interest in the therapeutic potential of the Nintendo Wii and Wii Fit (Wii) as Virtual Rehabilitation Therapy tools in conditions affecting motor function such as stroke, Parkinsons disease, ataxia, DCD, and cerebral palsy (CP). Although one case report showed significant gains in an adolescent with diplegic cerebral palsy, there was previously only a limited evidence base on use in children. This meta-analysis focused on RCTs in CP and aimed to calculate effect sizes to see if further trials are warranted. Methods: Eleven databases were used to find Wii RCTs. Studies were filtered by a focus on i) Cerebral Palsy ii) published 2006 – 2012 covering the availability of the Wii and iii) discounting broader virtual therapy. Effect size was calculated using Cohen's d. Effect size below 0.3 was classified as small, 0.3 to 0.8 medium and 0.8 + as large. Results: With the heterogeneous nature of CP a number of different tools and outcomes were measured in the different studies, and numbers were generally too small to give statistically significant results. However, two studies meeting criteria (N = 29, 14) showed effect sizes of 0.74 and 0.60 for balance. One study (n = 6) showed effect size 0.30 for motor function (GMFM). Other studies measured outcomes such as manual dexterity, bone mineral density or energy expenditure with variable results. Conclusion: The two studies assessing balance showed moderate effect sizes. This is in agreement with research looking at improvements in balance in other motor disorders including our own study in children with DCD, acquired brain injury, spinocerebellar ataxia, adults with stroke, and case reports in children with CP. Lack of uniformity across research hinders understanding of whether the Wii is effective paediatric intervention. Studies are predominantly pilot phase, lack agreement over measurement tools, use small sample sizes, and few had calculated power and sample size. Studies also suffer from selection bias due to the motivational aspects of the Wii. Nevertheless, results suggest there may well be significant therapeutic gain in motor function for children with cerebral palsy, warranting larger-scale and more definitive studies.